2018
DOI: 10.1128/aac.01799-17
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hsp90 Inhibitors with Anti-Plasmodium Activity

Abstract: Malaria remains a global health burden partly due to parasite resistance to first-line therapeutics. The molecular chaperone heat shock protein 90 (Hsp90) has emerged as an essential protein for blood-stage parasites, but details about its function during malaria's elusive liver stage are unclear. We used target-based screens to identify compounds that bind to and human Hsp90, which revealed insights into chemotypes with species-selective binding. Using cell-based malaria assays, we demonstrate that all identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 67 publications
1
33
2
2
Order By: Relevance
“…Activation of sporozoite intracellular calcium signaling cascades in response to the mammalian microenvironment was evident with increased abundance of calmodulin, CDPK7, protein kinase 4 (PK4), and Receptor of Activated Protein C Kinase 1 (RACK1). Our results also support recent reports that heat shock proteins (HSP) are critical for liver-stage parasite development as HSP70, HSP70-2, HSP90, and PVP01_1405400 were amongst the highest differentially expressed genes 51 . In order to rapidly transition between pivotal life-cycle stages, Plasmodium uses translational repression to regulate pre-transcribed mRNA stockpiles that encode required proteins.…”
Section: Resultssupporting
confidence: 91%
“…Activation of sporozoite intracellular calcium signaling cascades in response to the mammalian microenvironment was evident with increased abundance of calmodulin, CDPK7, protein kinase 4 (PK4), and Receptor of Activated Protein C Kinase 1 (RACK1). Our results also support recent reports that heat shock proteins (HSP) are critical for liver-stage parasite development as HSP70, HSP70-2, HSP90, and PVP01_1405400 were amongst the highest differentially expressed genes 51 . In order to rapidly transition between pivotal life-cycle stages, Plasmodium uses translational repression to regulate pre-transcribed mRNA stockpiles that encode required proteins.…”
Section: Resultssupporting
confidence: 91%
“…Despite the high sequence conservation amongst Hsp90 homologues of P. falciparum relative to their counterparts from humans and other species [17], their small differences may suffice to allow design of inhibitors which specifically target only the parasite’s Hsp90s [110]. It has been demonstrated that PfHsp90 (PF3D7_0708400) can be inhibited by a number of known Hsp90 inhibitors, and that growth of both the blood stages and liver stages is reduced by this treatment [56,59,110]. Among the tested inhibitors are GA, 17-DMAG, ganetespib, harmine, and PU-H71 [59,110].…”
Section: Implications For Therapeutic Interventionmentioning
confidence: 99%
“…In light of the importance of both PfHsp70-1 and PfHsp90 in the survival of the malaria parasite, there has been growing interest in identifying inhibitors targeting the function of these two molecular chaperones. Compounds that inhibit PfHsp70-1 [14; 15; 16] and PfHsp90 [17,9] have been identified, and some of them exhibit antiplasmodial activity. Some compounds that target PfHsp90 function reverse parasite resistance to traditional antimalarial drugs, such as chloroquine (reviewed in [18]).…”
Section: Introductionmentioning
confidence: 99%